Matching zooplankton abundance and environment in the South Indian Ocean and Southern Ocean. (September 2020) - Godet, Claire; Robuchon, Marine; Leroy, Boris; Cotté, Cédric; Baudena, Alberto; Da Silva, Ophélie; Fabri-Ruiz, Salomé; Lo Monaco, Claire; Sergi, Sara; Koubbi, Philippe
Abstract: Distinguishing regions based on the geographic distribution of both abiotic factors and living organisms is an old but still actual central issue for biogeographers. In the Southern Ocean, the few existing regionalization studies have been carried out either at very large scales or on the relatively small region around the Sub-Antarctic islands of Kerguelen and the Crozet archipelagos. However, regionalization studies at meso-scales (100–300 km) covering the Indian part of the Southern Ocean and adjacent South Indian Ocean are scarce. These waters, ranging from the Subtropical to the polar region, are home to large populations of well-studied top predators that depend on the biomass of less known mid-trophic level species such as zooplankton. To fill those gaps, our study aims at conducting bioregional analyses of this transition area at the meso-scale based on the distribution of abiotic factors and chlorophyll -a, and to investigate how the abundance of zooplankton varies across the bioregions identified. To that end, we first characterized epipelagic bioregions 30°S in the South Indian Ocean to 65°S in the Southern Ocean and from 40° to 85°E including the islands of Crozet, Kerguelen, Saint-Paul and New Amsterdam. We then determined whether these bioregions correspond to variations in the abundance of zooplankton collected by a Continuous Plankton Recorder. Finally, we analyzed which environmental parameters influence zooplankton abundance. Our analyses evidenced six regions, providing a synthetic overview of a contrasting environment. The spatial variability of zooplankton abundance was explained by most of the environmental variables used in the bioregionalisation and, to a lesser extent, by the bioregions. Copepods are abundant in the colder and physically-energetic regions associated with the Antarctic Circumpolar Current (ACC). Limacina and euphausids are both abundant in regions characterized by a high concentration of chlorophyll -a, although euphausids are also abundant in the subtropical region. This work represents a crucial step forward in the integration of living organism distribution in the regionalization of the Indian part of Southern Ocean and adjacent South Indian Ocean. This can, ultimately contribute to the optimization of marine conservation strategies. Highlights: Bioregionalization studies at mesoscale in the Southern/Indian Oceans are scarce. We delineated 6 pelagic bioregions in this area from environmental parameters. These bioregions are: the Shelf and high productivity off-shelf waters, the deep Eastern Part of the Enderby basin, the High turbulence areas of the Sub-Antarctic and Subtropical fronts, the Island shelves less productive areas and seamounts, the Indian Ocean Deep and the Indian ridges subtropical. Environmental parameters better explain variations in zooplankton abundance than bioregions.